Holistic person processing faces with bodies tell the whole story. [article]. - Aviezer, Hillel
Faces and bodies are typically encountered simultaneously, yet little research has explored the visual processing of the full person. Specifically, it is unknown whether the face anybody are perceived as distinct components or as an integrated, gestalt-like unit. To examine tis question, we investigated whether emotion face-body composites are processed in a holistic-like manner by using a variant of the composite face task, a measure of holistic processing. Participants judged facial expressions combined with emotionally congruent or incongruent bodies that have been shown to influence the recognition of emotion from the face. Critically, the faces were either aligned with the body in a natural position or misaligned in a manner that breaks the ecological person form. Converging data from 3 experiments confirm that breaking the the person from from reduces the facilitating influence of congruent body context as well as the impending influence of incongruent body context on the recognition of emotion from the face. These results show that faces and bodies are processed as a single unit and support the notion of a composite person effect analogous to the classic effect described for faces. - (from the authors)